A Modified Approach For Load Flow Analysis Of Integrated AC-DC Power Systems - Mustafa, M.W.; Abd Kadir, Aida Fazliana (2000)
High voltage direct current (HVDC) power distribution systems have been extensively used in modern transmission system. The major concern of the HVDC transmission is the loadflow in the system. This paper is dealing with the development of loadflow solution for a HVDC link in a power system. The loadflow solution is based on the fast decoupled method which needs some iteration to obtain the result. The paper exposed us to the integration of HVDC link with an AC power system. Variables of the direct current link which have been chosen for simulation are the converter terminal DC voltages, converter transformer tap ratios, firing angle of the rectifier and current in the HVDC link. An algorithm has been developed to solve the HVDC link power system loadflow and the algorithm has been tested on the IEEE test system